Explaining the Fast-Growing Textile and Garment Industries (TGI) in Vietnam (2000-2015) - Pertiwi, Sukmawani Bela (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2017)
The goal of this research is to explain the fast-growing textile and garment industries (TGI) in Vietnam from 2000 to present. This research is important in the context of Indonesia’s competition with Vietnam as among top TGI exporters in the world. This research adopted Gereffi’s Global Commodity Chains (GCCs) framework which situates TGI under the category of buyer-driven chains. Under this category, actors interested in industrial upgrading must develop both forward (marketing) and backward (production) linkages and learning process between this continuum. This research found that Vietnam’s fast growing textile and garment industries from 2000-present represents its successful industrial upgrading through its learning process in developing forward and backward linkages. Following these findings, therefore, Indonesia as competitor must also develop similar attitude and learning process in both linkages.